Experiencias y expectativas del familiar del paciente hospitalizado en la unidad de cuidados intensivos y la percepción del comportamiento de cuidado de la enfermera en el Hospital Base de la Red Asistencial Almenara, Lima - Martínez Ramón, Mirella Virginia (2019)
Objective: To establish the relationship between family experiences and expectations of the patient hospitalizedin the intensive care unit performance and perception of care received from the nurse at the Hospital NacionalGuillermo Almenara. 2011. 2011. Materials and Methods: This was a descriptive cross-sectional correlate. Lamuestra fue de 73 familiares, el muestreo fue no probabilístico por conveniencia para el estudio. The sample of 73families, the non-probabilistic sampling was convenience for the study. The collection instrument was a questionnaireconsisting of 27 items divided into three parts family’s previous experiences in the ICU, the family’s expectationsand perception of family UCI about the behavior of care. Results: 100% of the families they perceived as favorablebehavior of nursing care have had positive experiences and expectations, 97.4% of family members who perceivedthe behavior of nursing care and were equally indifferent experiences and expectations positive, while 81.2%of families perceived as unfavorable behavior of nursing care had positive experiences and expectations. Sóloun 18.8% de los familiares que percibieron como desfavorable el comportamiento de cuidado de las enfermerastuvieron experiencias y expectativas negativas. Only 18.8% of family members perceived as unfavorable behaviorof nursing care had negative experiences and expectations. Conclusions: The perception of the family about thebehavior of nursing care globally is irrelevant in the critical care unit followed by a favorable. Most families havepositive experiences and expectations, except for a negative experience on item to visit his patient out of hoursallowed. The vast majority of relatives who had had positive experiences and expectations of care perceptionsindifferent behavior. It was found that a significant association between these two variables (p <0.02).